Ответы и объяснения

2014-01-24T10:39:00+00:00
-(х+8)=3 
-х-8=3
-х=3+8
-х=11
х= -11

1-5(2-3х)=6
1-10+15х=6
15х=6-1+10
15х=15
х=15:15
х=1

7-3(х+1)=6
7-3х-3=6
3х=7-3-6
3х= -2
х= -2/3

5-2(3-х)=11
5-6+2х=11
2х=11-5+6
2х=12
х=12:2
х=6

2х-(7+х)=2
2х-7-х=2
х=2+7
х=9

-3-3(3-2х)=1

-3-9+6х=1
6х=1+3+9
6х=13
х=13/6
х=2  1/6
2014-01-24T10:42:49+00:00
1) -х-8=3
-х=3+8
-х=11
х=-11
2) 1-5(2-3х)=6
1-10+15х=6
-9+15х=6
15х=6+9
15х=15
х=15:15
х=1
3) 7-3(х+1)=6
7-3х-3=6
4-3х=6
4-6=3х
-2=3х
х=-2:3
х=-2/3(дробь)
4) 5-2(3-х)=11
5-6+2х=11
2х=11-5+6
2х=12
х=12:2
х=6